Perioperative Complication Profile of Skull Base Meningioma Resection in Older versus Younger Adult Patients - Przybylowski, Colin J.; Shaftel, Kelly A.; Hendricks, Benjamin K.; Chapple, Kristina M.; Stevens, Shawn M.; Porter, Randall W.; Sanai, Nader; Little, Andrew S.; Almefty, Kaith K. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objectives To better understand the risk-benefit profile of skull base meningioma resection in older patients, we compared perioperative complications among older and younger patients.Design Present study is based on retrospective outcomes comparison.Setting The study was conducted at a single neurosurgery institute at a quaternary center.Participants All older (age ≥ 65 years) and younger (<65 years) adult patients treated with World Health Organization grade 1 skull base meningiomas (2008–2017).Main Outcome Measures Perioperative complications and patient functional status are the primary outcomes of this study.Results The analysis included 287 patients, 102 older and 185 younger, with a mean (standard deviation [SD]) age of 72 (5) years and 51 (9) years (p < 0.01). Older patients were more likely to have hypertension (p < 0.01) and type 2 diabetes mellitus (p = 0.01) but other patient and tumor factors did not differ (p ≥ 0.14). Postoperative medical complications were not significantly different in older versus younger patients (10.8 [11/102] vs. 4.3% [8/185]; p = 0.06) nor were postoperative surgical complications (13.7 [14/102] vs. 10.8% [20/185]; p = 0.46). Following anterior skull base meningioma resection, diabetes insipidus (DI) was more common in older versus younger patients (14 [5/37] vs. 2% [1/64]; p = 0.01). Among older patients, a decreasing preoperative Karnofsky performance status score independently predicted perioperative complications by logistic regression analysis (p = 0.02). Permanent neurologic deficits were not significantly different in older versus younger patients (12.7 [13/102] vs. 10.3% [19/185]; p = 0.52).Conclusion The overall perioperative complication profile of older and younger patients was similar after skull base meningioma resection. Older patients were more likely to experience DI after anterior skull base meningioma resection. Decreasing functional status in older patients predicted perioperative complications.
Keywords: elderly; frailty; meningioma; skull base